Resilience and performance in mathematics of the child of San Juan de Lurigancho - Rodríguez Castillo, Marcos Fabris (2018)
The purpose of the study was to test the hypothesis of relationship between resilience and academic performance in mathematics of schoolchildren in San Juan de Lurigancho, Lima, quantitative study, transectional correlational level, in a probabilistic sample of 350 students of sixth grade of primary school, were used the IRES resilience instrument and performance test in mathematics; a relationship was determined between the variables in children with performance achievement in mathematics (A) (r =, 458), and in achievement (B) (r =, 324) in a significant way, in the same way high coefficient of relationship was corroborated of performance in mathematics and coping, optimism, and goal orientation; Finally, it is suggested to compare samples by the level of social aggressiveness and criminal attitudes.